Penerapan Pandangan Aliran Filsafat Esensialisme Pada Pembelajaran Matematika : Application of the Essentialism Philosophy Viewpoint in Mathematics Learning - Setyaningrum, Lika; Fitriana, Laila; Nugroho, Hery (Undiksha, 2025)
The preparation of a learning method is based on a clear foundation, one of which is by applying philosophy schools in education. There are seven main philosophical schools of education used in the preparation of learning methods. One of them is the philosophy of essentialism which prioritizes cultural cultivation in education and is also used in learning, especially in mathematics lessons. This study aims to describe the application of the view of the philosophy of essentialism to ethnomathematics-based mathematics learning. The researchers used a qualitative method with a literature study. Furthermore, the data collection technique is by collecting and analyzing data with bibliographic annotations. Data analysis consists of data reduction, data presentation, and conclusion/verification. The findings show that the philosophy of the essentialism school directs education in cultural and discipline cultivation to students, especially in mathematics learning with ethnomathematics-based learning. The development of ethnomathematics-based learning is influenced by one of the philosophies of education, namely the philosophy of the essentialism school. Education that forms cultured human beings and the knowledge learned can be useful in daily life is the same goal of the philosophy of the school of essentialism and ethnomathematics.